AI-Driven Development Is Here: Should You Worry? - Ernst, Neil A.; Bavota, Gabriele; Menzies, Tim (IEEE software, 2022)
Artificial Intelligence Driven Development Environments (AIDEs) integrate the power of modern AI into IDEs like Visual Studio Code and JetBrains IntelliJ. By leveraging massive language models and the plethora of openly available source code, AIDEs promise to automate many of the obvious, routine tasks in programming. At the same time, AIDEs come with new challenges to think about, such as bias, legal compliance, security vulnerabilities, and their impact on learn programming.